Cryoballoon catheter ablation or drug therapy to delay progression of atrial fibrillation: A single-center randomized trial - Ding, Jun; Cheng, Aijuan; Li, Peng; Yan, Yingchuan; Shi, Yutian; Xue, Zuochen; Sun, Shan; Xu, Jing (Frontiers in Cardiovascular Medicine, 2022)
Background: Delaying atrial fibrillation (AF) progression is a key goal in cardiovascular treatment. However, numbers of previously published studies on delayed AF progression are relatively limited. The purpose of this study was to determine whether a cryoballoon catheter ablation (CA) strategy could delay AF progression compared to anti-arrhythmic drug (AAD) treatment in patients with paroxysmal AF. Methods: A total of 204 subjects were enrolled in the trial, including 102 in the cryoballoon CA group and 102 in the AAD group. Participants were followed up with for 36 months. The primary study endpoint was the first occurrence of persistent atrial tachyarrhythmias, while secondary endpoints included the event rates of persistent atrial tachyarrhythmia at 1 and 2 years. The primary safety endpoint was serious adverse events. Results: Overall, the 36-month follow-up was completed by 154 subjects (75.5%). At 3 years, documented progression from paroxysmal to persistent AF had occurred in 2 of the 102 patients assigned to undergo cryoballoon CA (2.203% [95% confidence interval [CI], 0.554–8.537]) and in 17 of the 102 patients assigned to receive AADs (20.223% [95% CI, 13.040–30.604]) (hazard ratio [HR], 0.107; 95% CI, 0.043–0.262; P < 0.001). Lower rates of progression in the cryoballoon CA group compared to the AAD group were already obvious at 1 year (1.053% [95% CI, 0.149–7.238] vs. 5.284% [95% CI, 2.233–12.237]) (HR, 0.193; 95% CI, 0.039–0.956; P = 0.09]) and 2 years (2.203% [95% CI, 0.554–8.537] vs. 12.430% [95% CI, 7.066 to 21.371]) (HR, 0.169; 95% CI, 0.057–0.501’ P < 0.001). Serious adverse events occurred in 7 of the 102 patients (6.9%) in the cryoballoon CA group and 6 of the 102 patients (5.9%) in the AAD group. Conclusion: Cryoballoon CA was superior to AAD therapy in preventing progression from paroxysmal to persistent AF in patients with paroxysmal AF who had not received prior rhythm control therapy. Serious adverse events were rare.